PENGARUH POLA PENGGERGAJIAN DAN SUDUT SAYAT TERHADAP RENDEMEN DAN PRODUKTIVITAS PENGGERGAJIAN KAYU NIBUNG (ONCOSPERMA TIGILLARIUM) - Osly Rachman; Dede Rohadi (Jurnal Penelitian Hasil Hutan, 1987)
Nibung (Oncosperma  tigillarium) is a member of palm family which has a good potential for  utilization. An experiment to find out the best sawing pattern and hook angle of saw blade for  better recovery and sawing productivity was conducted. Two sawing patterns (live sawing and sawing around)  and two hook  angles (20 and 27 degrees were applied).The results indicated that sawing around pattern produced higher recovery of hard and medium  wood than live sawing as much as 8%, while the 27° of  hook  angle produced higher productivity than 20°  angle as much  as 0.30  m2/min.